The analysis of barriers for implementing circular economy practices using the Analytic Hierarchy Process (AHP) - Santos, Hugo Henrique; Marques, Vitor Natã; Paschoali, Luiz Felipe Ferreira (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – This paper aims to identify and classify the main barriers for adopting circular economy practices using the Analytic Hierarchy Process (AHP) method for prioritization. The proposed methodology evaluates the importance of different classes of barriers for adopting circular economy practices in a food company and metalworking company. Theoretical framework – This study was based on the current theory of barriers to adopt circular economy practices and multicriteria decision-making. Design/methodology/approach – The Analytic Hierarchy Process (AHP) method was used to assess and prioritize barriers for circular economy practices. Stability was ranked using a sensitivity analysis. Findings – The results indicate significant differences in the classification of barriers. While the food manufacturing company indicate that the main barriers are related to technical information, the metalworking company considered that barriers relating to financial and economic issues have more of an impact. Originality/value – The study contributes to providing insights so that managers have a greater perception of the main difficulties in adopting circular economy practices, in addition, the study also contributes to extending the application of multicriteria decision making methodologies to the circular economy and evaluating the relative importance of the barriers. Keywords - Circular Economy; Analytic Hierarchy Process; multicriteria analysis; barriers; sustainable development.